Chronic adenoiditis - Wang, Hai (Journal of international medical research, 2020)
In addition to acute adenoiditis and adenoid hypertrophy/vegetation, chronic adenoiditis is another disease of the adenoids. However, most physicians overlook chronic adenoiditis or confuse it with adenoid hypertrophy/vegetation. The incidence of chronic adenoiditis has increased in recent years as a result of higher rates of chronic nasopharyngeal or upper airway infections. The clinical characteristics of chronic adenoiditis can include but are not restricted to the following: long-term infection (especially bacterial infection); obstruction of the upper airway; infections of adjacent regions, such as the nose, nasal sinus, pharyngeal space, middle ear, and atlantoaxial joint; induced upper airway cough syndrome; and the presence of several “infectious-immune” diseases, including rheumatic fever, autoimmune nephropathy, and anaphylactoid purpura. To date, no consensus on the treatment of chronic adenoiditis is available. However, adenoidectomy can address the local obstruction, and some patients benefit from systemic or local anti-bacterial therapy. Physicians in the Departments of Otolaryngology, Respiration, and Pediatrics should be familiar with the clinical manifestations of chronic adenoiditis and try to develop effective treatment methods for this disease.